Neurosyphilis in patients at a university hospital in the central west region of Brazil - Wander Rosa, Pâmella; Alves Santa Barbara Borges, Moara; Soares Coriolano Coutinho, João Víctor; Vieira Teles-Filho, Ricardo; Oliveira Guilarde, Adriana (Revista de Patologia Tropical / Journal of Tropical Pathology, 2023)
Syphilis remains a significant public health concern, and the central nervous system (CNS) involvement may occur at any stage of infection. Neurosyphilis must be ruled out in patients diagnosed with syphilis and exhibiting neurological or psychiatric symptoms, and cerebrospinal fluid (CSF) examination should be performed prior to treatment. A cohort of patients with neurosyphilis (aged ≥18 years old) was studied in a university hospital in the Central West Region of Brazil from 2018 to 2021. Twenty-four patients met the criteria for inclusion of confirmed neurosyphilis; 17 (70%) were male, with a median age of 37.5 (22–64). Six were asymptomatic, one had isolated otosyphilis, 11 had ocular syphilis, one had both ocular and otosyphilis, and five had other neurological symptoms. Thirteen patients (54%) were coinfected with HIV. Visual changes (50%) were the most common symptom; otosyphilis was present in 8.3%. Fourteen patients (58%) had positive VDRL in the CSF, and the median CSF-VDRL titer was 1:4. The cure rate was 87%, with three cases having persistent CSF-VDRL positivity after six months from the first treatment. It was concluded that understanding neurosyphilis, its clinical diversity, and its epidemiological and laboratory profile allows early diagnosis and treatment, consequently reducing its morbidity. KEY WORDS: Syphilis; neurosyphilis; otosyphilis; ocular syphilis; HIV.